Leveraging Analytics to Drive Human Performance - Forest, Denis; Bahlis, J. (Jay) (International Journal of Advanced Corporate Learning (iJAC), 2025)
Recent audit reports by the Auditor General noted the potential impact to Canadian Armed Forces readiness due to sub optimal Defence Supply Chain performance. To identify the root cause of performance deficiencies and assess the adequacy of existing training, a systematic approach was employed to identify the knowledge and skills required by each Supply Chain role to perform their share of tasks across 39 Processes. Based on the Department of National Defence Supply Administration Manual (SAM), the project team mapped Processes and Tasks to all applicable Supply Chain Phases. Processes and Tasks were also mapped to each role and the training priority was determined based on Difficulty, Importance and Frequency (DIF) analysis. We then mapped topics/teaching points from relevant course to existing processes and Tasks; and generated a list of processes and Tasks with “adequate”, “limited” or “no” curriculum to support the acquisition of requisite knowledge and skills for each role. The analysis revealed: • All roles contribute heavily to the overall success of the Supply Chain in an integrated work environment – necessitating an understanding of the impact of their work on others. • Developing curriculum incrementally over the years based on specific, sometimes narrow needs/performance and without a comprehensive map as outlined above yielded inefficient learning solutions. • Developing role-based solutions in parallel with process-based curriculum resulted in gaps and duplication of effort. This paper reaffirms the need for “getting back to basics”. A thorough analysis and mapping of actual work/role requirements based on an authoritative reference, using a systematic process enabled by a leading-edge Training Management System, will provide a robust analysis framework. Training gaps and overlaps will become evident, and a blueprint for a comprehensive re-organization of the curriculum will naturally emerge.